2022
DOI: 10.1051/matecconf/202236105010
|View full text |Cite
|
Sign up to set email alerts
|

Self-healing of concrete containing commercial bacteria by means of water and chlorides permeability

Abstract: Microbial-induced calcium precipitation (MICP) has shown adequate potential to act as a healing product through Calcium Carbonate (CaCO3) precipitation inside cracks. This work studies the self-healing capability of conventional concrete incorporating two dosages of Bacillus subtilis encapsulated in diatomaceous earth and a liquid solution consisting of a combination of Bacillus, denitrifying, and photosynthetic bacteria. The two bacterial agents used are commercial or industrial products from other sectors. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…A modified water penetration test proposed in previous studies [56,57] was performed by measuring the penetration of sodium chloride through the crack's path and the concrete surface by using its reaction with silver nitrate as a pigmentation method to detect the penetration.…”
Section: Chloride Penetration Testmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified water penetration test proposed in previous studies [56,57] was performed by measuring the penetration of sodium chloride through the crack's path and the concrete surface by using its reaction with silver nitrate as a pigmentation method to detect the penetration.…”
Section: Chloride Penetration Testmentioning
confidence: 99%
“…As expected, specimens healed in HC had P 0 values like the reference of uncracked specimens (Ref P 0 ). Research on selfhealing already reported the substantial effect of water in healing [41,57], and Escoffres et al [69] proposed that specimens healed in a humidity chamber can be used as references since in practice, HC do not promote healing. Healed HPC specimens had a penetration below 2 mm in all mixes, as in the uncracked specimens.…”
Section: Penetration Through the Matrixmentioning
confidence: 99%
“…A modified chloride permeability test presented in previous studies [17,18] was performed. This test provides information about the penetration of chlorides throughout the healed crack path and the matrix.…”
Section: Low-pressure Water Permeability Testmentioning
confidence: 99%
“…These polymers can absorb large amounts of water and their consequent swelling capacity allows them to (partially) block cracks. [3,[8][9][10][11] Additionally, they can release this water in drier periods, thereby promoting the concrete's autogenous self-healing mechanisms. [9][10][11] The crack size that can be healed is however limited as well to cracks <0.2 mm.…”
Section: Introductionmentioning
confidence: 99%
“…[3,[8][9][10][11] Additionally, they can release this water in drier periods, thereby promoting the concrete's autogenous self-healing mechanisms. [9][10][11] The crack size that can be healed is however limited as well to cracks <0.2 mm. [8] Autonomous self-healing methods require a self-healing agent, such as specific bacteria and fungi capable of CaCO 3 -producing biomineralization.…”
Section: Introductionmentioning
confidence: 99%